Importance and Necessity of Peace Education in the School Curriculum for Fostering International Perspective - Manzoor Bhat, Rashid; Laxmi Jamatia, Purna (RADJA PUBLIKA, 2022)
The rise of materialism and militarism was promoted by the industrial revolution. Indirectly, militarism affected the outbreak of war by encouraging the growth of the armaments industry. In order to create the reality of battle, cultural and educational manipulations are used to reinforce group identification and build images of the enemy as well as their possibilities. Denial of human values leads to the death of innocent civilians, especially children and women, as a result of the tendency to dehumanise the enemy. Love, camaraderie, and worldwide understanding are instilled and built via Peace Education. The term